2017
DOI: 10.1016/j.ajpath.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Active mTOR Mutation in Brain Malformation with Intractable Epilepsy Leads to Cell-Autonomous Migration Delay

Abstract: The activation of phosphatidylinositol 3-kinase-AKTs-mammalian target of rapamycin cell signaling pathway leads to cell overgrowth and abnormal migration and results in various types of cortical malformations, such as hemimegalencephaly (HME), focal cortical dysplasia, and tuberous sclerosis complex. However, the pathomechanism underlying abnormal cell migration remains unknown. With the use of fetal mouse brain, we performed causative gene analysis of the resected brain tissues from a patient with HME and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…These findings are reminiscent to what has been observed for mutations of MTOR itself. Constitutive activation of mTORC1 causes enlarged neuronal somata in rodent neurons, and focal cortical expression of MTOR mutations has been reported to disrupt neuronal migration and to cause spontaneous seizures by in utero electroporation in mice 40 , 41 , 53 . This observation shows that activating mutations in different genes of the mTORC1 branch of the mTOR pathway act through convergent mechanisms and have similar phenotypic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are reminiscent to what has been observed for mutations of MTOR itself. Constitutive activation of mTORC1 causes enlarged neuronal somata in rodent neurons, and focal cortical expression of MTOR mutations has been reported to disrupt neuronal migration and to cause spontaneous seizures by in utero electroporation in mice 40 , 41 , 53 . This observation shows that activating mutations in different genes of the mTORC1 branch of the mTOR pathway act through convergent mechanisms and have similar phenotypic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, the role of signals that regulate hamartin and tuberin activity as well as the mTORC1 substrates responsible for specific developmental events are only now being determined. Perhaps most striking is the fact that somatic mutations that cause mTORC1 pathway activation have been identified as a cause of a plethora of neurological diseases (Lee et al, 2012 ; Poduri et al, 2012 ; Parker et al, 2013 ; Lal et al, 2014 ; Baek et al, 2015 ; Baulac et al, 2015 ; Crino, 2015 ; D’Gama et al, 2015 , 2017 ; Leventer et al, 2015 ; Lim et al, 2015 ; Baulac, 2016 ; Korenke et al, 2016 ; Møller et al, 2016 ; Hanai et al, 2017 ; Park et al, 2018 ; Iffland and Crino, 2019 ; Kim et al, 2019 ; Pelorosso et al, 2019 ; Salinas et al, 2019 ; Zhao et al, 2019 ; Garcia et al, 2020 ). Thus, what has been learned by studying the TSC pathway may now be applied to an expanding number of patients.…”
Section: The Molecular Genetics Of Tscmentioning
confidence: 99%
“…This study demonstrated that the change of the conserved aspartic acid in position 2412 to valine is a gain-of-function variant (GOF) since it was able to activate the mTOR pathway (Fig. 3) [17]. Thus, the phosphorylation of the mTORC1 substrates 4EBP1 and S6K, and phosphorylation of AKT, the substrate of mTORC2, were increased in patient, indicating activation of both complexes.…”
Section: Discussionmentioning
confidence: 81%